Imaging of the Acetabular Labrum - Thomas, James D.; Li, Zhi; Agur, Anne M.; Robinson, Philip (Seminars in Musculoskeletal Radiology, 2013)
The evaluation and proposed relevance of acetabular labral tears has rapidly evolved over the last decade due to the recognition of femoroacetabular impingement, an increase in the number of surgical options, and improved imaging of the hip with MR arthrography and 3-T MR protocols. The acetabular labrum, stabilizing the hip joint, provides a seal, enhancing fluid lubrication, maintains synovial pressure, and prevents direct contact of the articular surfaces. The labrum takes on a weightbearing role at the extremes of motion with excessive forces seen in a great number of athletic activities thought to contribute to tearing. Approximately 25% of labral tears are not associated with any specific injury or traumatic event with the underlying etiology thought to be repetitive microtrauma. This article reviews the anatomy of the acetabular labrum and discusses the five most commonly occurring etiologies of labral tears: trauma, femoroacetabular impingement, hip hypermobility, dysplasia, and degeneration. We also review the surgical and MR classification of labral tears and describe potential pitfalls in image interpretation.
Keywords: hip; MRI; MR arthrography; labrum